2011
DOI: 10.1371/journal.ppat.1002235
|View full text |Cite
|
Sign up to set email alerts
|

The General Transcriptional Repressor Tup1 Is Required for Dimorphism and Virulence in a Fungal Plant Pathogen

Abstract: A critical step in the life cycle of many fungal pathogens is the transition between yeast-like growth and the formation of filamentous structures, a process known as dimorphism. This morphological shift, typically triggered by multiple environmental signals, is tightly controlled by complex genetic pathways to ensure successful pathogenic development. In animal pathogenic fungi, one of the best known regulators of dimorphism is the general transcriptional repressor, Tup1. However, the role of Tup1 in fungal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 95 publications
3
36
0
1
Order By: Relevance
“…The change in morphology between yeast-like growth and a filamentous state in response to environmental signals is frequently associated with virulence in plant pathogenic fungi [106]. TUP1 plays a central role in controlling the expression of the genes implicated in the genetic control of mating, filamentation, and pathogenic development of Ustilago maydis [108]. Analyzing the function of TUP1 in rust fungi could provide a better understand of how it acts within the unique biological context in which these pathogens develop.…”
Section: Resultsmentioning
confidence: 99%
“…The change in morphology between yeast-like growth and a filamentous state in response to environmental signals is frequently associated with virulence in plant pathogenic fungi [106]. TUP1 plays a central role in controlling the expression of the genes implicated in the genetic control of mating, filamentation, and pathogenic development of Ustilago maydis [108]. Analyzing the function of TUP1 in rust fungi could provide a better understand of how it acts within the unique biological context in which these pathogens develop.…”
Section: Resultsmentioning
confidence: 99%
“…The important role of Tup1/TupA in pathogenic fungi has received further attention because of its important role in dimorphism and pathogenicity. Although the role of Tup1 in fungal dimorphism is conserved, the way it controls the switch differs between fungi [12], [31][33].…”
Section: Introductionmentioning
confidence: 99%
“…Tup1 homologues have also been studied in filamentous fungi and are implicated in switching of cell growth, conidiation and pathogenesis in Neurospora crassa (Yamashiro et al, 1996), Candida albicans (Braun and Johnson, 1997, 2000), Aspergillus nidulans (Hicks et al, 2001), Penicillium marneffei (Todd et al, 2003), Cryptococcus neoformans (Lee et al, 2005, 2009) and Ustilago maydis (Elías-Villalobos et al, 2011). These studies on some phenotypes suggested that Tup1 homologues activate the expression of certain genes.…”
Section: Discussionmentioning
confidence: 99%
“…Tup1 homologues are conserved throughout eukaryotes (Courey and Jia, 2001) and have been demonstrated to regulate gene expression in a wide variety of cellular processes, including metabolic change, asexual and sexual development, responses to environmental signals and developmental switching (Elías-Villalobos et al, 2011; Hicks et al, 2001; Long et al, 2006; Todd et al, 2003; Yamashiro et al, 1996). …”
Section: Introductionmentioning
confidence: 99%